Electronic Voting System Essentials and Problems - Avetisyan, Arman A. (Изд-во НАН РА)
The development of reliable and safe e-voting systems is relevant because of the widerange of applications. This paper provides an analysis of modern electronic voting systems based on security criteria. An analysis was conducted based on the mostpopular modern e-voting system architectures. The analysis provides a baseline fordeveloping a secure e-voting system.
Keywords: Mathematical cybernetics; Computer science